KEPATUHAN IMUNISASI DASAR PADA BAYI: APAKAH JARAK PELAYANAN KESEHATAN DAN TOKOH MASYARAKAT BERPENGARUH? - Aisyah, Aisyah; Alhidayah, Alhidayah; Siswoko, Siswoko; Pasiriani, Novi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Based on global data, approximately 11 million children under the age of 5 die each year, a very high number that highlights a major challenge in fulfilling children's health rights. The objective of this study is to determine the distance between health services and community leaders and immunization compliance. The research design used in this study is cross-sectional. The study was conducted at the Lelogama Community Health Center in September 2024. The study population consisted of all mothers with infants aged 9–24 months, totaling 219 individuals. The sample size was 70 individuals. The sampling technique used in this study was purposive sampling. Data analysis was performed using univariate and bivariate methods. The results of the study showed a relationship between the distance to health services (p-value: 0.002) and community leader support (p-value: 0.044) with immunization compliance. It is recommended that the Community Health Center (Puskesmas) improve the compliance rate of mothers in bringing their infants to the Posyandu by increasing mothers' knowledge through socialization by local Posyandu cadres about the importance of the Posyandu program, the benefits of Posyandu, and the consequences if mothers do not comply in bringing their infants to Posyandu. There needs to be collaboration between the Puskesmas and the local village authorities to regularly refresh the cadres' knowledge and provide rewards to active cadres.Keywords: Immunization, Distance, Community Leaders.